Physico‐Chemical, antioxidant activities, textural, and sensory properties of yoghurt fortified with different states and rates of pomegranate seeds (Punica granatum L.). Issue 3 (20th December 2019) - Bchir, Brahim; Bouaziz, Mohamed Ali; Blecker, Christophe; Attia, Hamadi
Abstract: This study examines the effects of incorporating fresh, frozen, osmodehydrated, and dried pomegranate seeds, at different concentrations (5, 10, and 20%) on the physicochemical, antioxidant, textural, and sensory properties of yoghurt. Antioxidant activity, pH, acidity, syneresis, and color of yoghurt were also evaluated during the storage (28 days) at 4°C. The principal component analysis (PCA) was performed to assess the correlations between different yoghurt formulation and their sensory attributes. Data showed that the addition of pomegranate seeds reduced pH and modified the chromatics coordinate ( L *, a *, b *, C *, h °) and firmness of the yoghurt samples. In addition, acidity, °Brix, and syneresis increased compared to the control. Thanks to their high anthocyanin content, pomegranate seeds considerably improved the antioxidant activity essentially for yoghurt enriched with frozen seeds. In addition, the supplementation of 20% of frozen seeds into yoghurt was the most appreciated by panelists and improved the sensory properties in comparison to other formulation. According to PCA, taste and appearance were the main criteria for the overall acceptability of yoghurt. After 28 days of storage, the reddish color was reinforced; however, the antioxidant activity of yoghurts was reduced. Overall, it can be concluded that pomegranate seeds can be used as a natural ingredient to develop a novel yoghurt with high nutritional properties.